Effects of organic fertilizers on growth and yield of Roselle (Hibiscus sabdariffa L.) on BRIS soil - Norhayati Y.,; Ng, W.H.; Adzemi M.A., (Penerbit Universiti Kebangsaan Malaysia, 2019)
The application of organic fertilizers on roselle has generated much interest among the researchers and farmers for the past two decades. However, little attention is given on the plantation quality in Beach Ridges Interspersed with Swales (BRIS) soil. Roselle is generally preferred because it is rich in ascorbic acid and anthocyanin that are very beneficial for health. This study determined the growth, yields and antioxidants of roselle on BRIS soils after application with different rate of organic fertilizers. Roselle was treated with five different rates of goat manure i.e. T1 (control), T2 (40 mt/ha), T3 (80 mt/ha), T4 (120 mt/ha) and T5 (160 mt/ha). Plant growth, yields and antioxidants of roselle calyxes were determined at three weeks interval for 21 weeks. Generally, organic fertilizer treated roselle showed significant increased (p<0.05) plant growth and plant yield. Higher rate of organic fertilizer, particularly T5 (160 mt/ha) increased the stem diameter and stem height, leaves number and leaves area as well as the biomass and number of calyx. Organic fertilizer treatments had no significant effect on ascorbic acid, carotenoids and anthocyanin production except for T3 treated plants whereas, chlorophyll content was significantly induced (p<0.05) in response to organic fertilizer treatments. In conclusion, application of organic fertilizers at higher rate showed positive effects on the growth, yield and antioxidant content of roselle. Therefore, organic fertilizer should be frequently applied in the farms to get the best growth and yields of the plant.